Theory and practice of industrial policy : evidence from the Latin American experience - Peres, Wilson (CEPAL SantiagoCL, 2009)
Attempts to define the concept of industrial policy, to review certain relevant historical experiences, and to examine the current state of the art of industrial policy in Latin America.